PREMARITAL CHECK UP DI INDONESIA (Studi kasus di Kantor Urusan Agama Kecamatan Pare Kabupaten Kediri) - Arianto; Muhammad Rifki Ghufron (Institut Agama Islam Hasanuddin Pare, 2024)
Currently, it is not only tetanus that we need to be aware of, but now many dangerous infectious diseases have emerged for which no cure has yet been found, such as HIV/AIDS which has claimed many lives. The medical world has made recommendations to prospective brides and grooms who want to get married to carry out a premarital health check-up first. Carrying out a health check before marriage is a form of prevention to maintain health, especially for its impact on offspring. The type of research used in this research is field research, namely research carried out directly on events and data in the field, in this case the author conducted research at the KUA and Pare District Health Center, Kediri Regency. This research includes empirical normative research, namely research conducted by examining the implementation or implementation of legal provisions which are conceptualized as norms or rules that apply in society and become a reference for everyone's behavior. Premarital check-ups or pre-marital health checks have actually been implemented through Tetanus Toxoid Immunization. Its implementation is carried out based on the Joint Instructions of the Director General of Islamic Community Guidance and Hajj Affairs, Department of Religion and Environmental Health, Department of Health No: 02 of 1989 concerning Tetanus Toxoid Immunization of Prospective Brides and as the basis for the implementation of Law No. 1 of 1974, as well as Presidential Instruction No. 1 of 1991 concerning the Compilation of Islamic Law